Facile Synthesis of MOF‐Derived One‐Dimensional Nitrogen‐doped Carbon/Ni Composites and their Application as Catalysts and Protein Adsorbents. Issue 19 (18th May 2022) - Pan, Wentao; Zheng, Jing; Du, Hong; Zhang, Baishun; Xu, Jingli; Zhang, Min
Abstract: Metallic nickel is of particular interest because of its low cost, magnetic property, and multifunctional uses. Herein, a facile strategy to fabricate one dimensional(1D) carbon microrods with magnetic Ni nanoparticles(NPs) by one‐step carbonization of nickel‐ion‐nitrilotriacetic acid coordination polymer microrods (Ni‐NTA) has been presented. After the carbonization, the original morphology of Ni‐NTA microrods is preserved well. Fine magnetic Ni NPs are well dispersed in the carbon matrix, which possesses an impressive saturation capacity for Histidine‐rich protein, BHb. Moreover, such N‐doped carbon microrods with well‐dispersed Ni NPs on its surface present an excellent catalytic performance and stability by using the reduction of 4‐nitrophenol as a model reaction. Notably, the selected Ni‐NTA microrods and melamine act as Ni‐precursor and N‐doped carbon sources play a vital role in the formation of 3D hierarchical carbon dendrites composed of carbon microfiber trunks and carbon nanotube branches. Abstract : Herein, a facile strategy to fabricate one dimensional carbon microrods with magnetic Ni nanoparticles by one‐step carbonization of nickel‐ion‐nitrilotriacetic acid coordination polymer microrods (Ni‐NTA) has been presented. Fine magnetic Ni NPs are well dispersed in the carbon matrix, which possesses an impressive saturation capacity for histidine‐rich protein, BHb. Moreover, such N‐doped carbon microrods present an excellent catalytic performance in the reduction of 4‐nitrophenol.